Entropy of fermionic models on highly frustrated lattices - Honecker, A.; Richter, J. (Condensed Matter Physics, 2005)
Spinless fermions on highly frustrated lattices are characterized by the lowest single-particle band which is completely flat. Concrete realizations are provided by the sawtooth chain and the kagome lattice. For these models ´ a real-space picture is given in terms of localized states. Furthermore, we find a finite zero-temperature entropy for a suitable choice of the chemical potential. The entropy is computed numerically at finite temperature and one observes a strong cooling effect during adiabatic changes of the chemical potential. We argue that the localized states, the associated zerotemperature entropy as well as the large temperature variations carry over to the repulsive Hubbard model. The relation to flat-band ferromagnetism is also discussed briefly.